Pengaruh Current Ratio, Perputaran Persediaan, Debt To Asset Ratio, Growth Dan Size Terhadap Profitabilitas Perusahaan Retail Sektor Trade, Investment dan Service Yang Terdaftar di Bursa Efek Indonesia - Annisa Nauli Sinaga; Citra William; Tiffanny Meiluartha; Alviana Celia Jansen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The development of companies nowadays have been growing rapidly and causing intense competition in the market. Trade, service, and investment sector companies are emerging in Indonesia. Thus, this study aims to identify the impact of current ratio, inventory turnover, debt to asset ratio, growth and size towards firm’s profitability in Trade, Service, and Investment Companies Listed in Indonesia Stock Exchange (IDX) from year 2016-2019. The research type of this study is quantitative method. The data is classified as quantitative and ratio scale. This study uses secondary data. The population for this study is 154 trade, service, and investment sector companies listed in Indonesia Stock Exchange (IDX) from year 2016-2019. The sample for this study is 65 trade, service, and investment sector companies listed in Indonesia Stock Exchange (IDX) from year 2016-2019 using observational sampling method. The model of this study is multiple linear regression. The result of this study shows that current ratio, inventory turnover, debt to asset ratio, growth and size partially and simulteneously do not affect firm’s profitability in Trade, Service, and Investment Companies Listed in Indonesia Stock Exchange (IDX) from year 2016-2019. Keywords : Current Ratio, Inventory Turnover, Debt To Asset Ratio, Growth, Size dan Profitability